Stakeholders’ views on addressing adverse childhood experiences in the Maghreb: A participatory approach - Fadi Baghdadi (Children and Youth Services Review, 2025)
BackgroundAdverse Childhood Experiences (ACEs) are traumatic events with lasting impacts on health and wellbeing into adulthood. Countries in the Maghreb have some of the highest rates of ACEs in the world, though there is minimal local research from the region.ObjectiveTo gather perspectives from local stakeholders to inform the development of effective and sustainable local programmes that address the high rates of ACEs across the Maghreb.Participants and settingWe conducted nine Participatory Learning and Action (PLA) workshops with 86 stakeholders in Nouakchott (Mauritania), Taroudant (Morocco) and Mahdia (Tunisia). We conducted three PLA workshops in each country with: 1) Parents of children at risk of ACEs (n = 29); 2) Non-governmental organisations staff (n = 31); and 3) Senior professionals (n = 26).MethodsPLA workshops consisted of Participatory Rank Methodology (PRM) activities to understand the factors influencing children’s exposure to ACEs and a case vignette activity to understand stakeholders’ perceptions of the available resources to protect children from ACEs. We coded and analysed data using thematic and narrative analysis.ResultsFactors influencing children’s exposure to ACEs highlighted by stakeholders through the PRM exercises included parenting skills, access to services, and marginalisation of single mothers and their children. Responses to case vignettes varied by country, with stakeholders in Mauritania and Tunisia expecting response from government and community networks, while in Morocco the emphasis was on community networks only.ConclusionLocal stakeholders proposed strengethening community networks to mitigate ACEs in the Maghreb. Findings demonstrate the importance of family stability, accessible government services, and community support for reducing children’s exposure to ACEs. Further research is required to develop tailored programmes addressing regional challenges.